The influence of social media, product quality, and product price on the purchase intentions of students in surakarta: a study on halal cosmetics (skincare) - Signori, Muhammad; Sholahudin, Muhammad (Institute of Computer Science (IOCS), 2024)
Population growth in Indonesia is accompanied by an increase in the number of internet users. Social media has become a means for sharing information and conducting business. Social media platforms provide a viable avenue for marketing and selling skincare products. Through social media, sellers can inform consumers about product quality through product descriptions and reviews from previous buyers. In addition to quality, social media can also provide information about product prices. The quality and price of products listed on social media can influence the purchase intentions of potential consumers. The aim of this study is to determine whether social media, product quality, and product price influence the purchase intentions of students in Surakarta regarding halal cosmetics (skincare). This research employs a quantitative research method with an observational approach involving 150 respondents. Data collection was processed by distributing questionnaires to the respondents. The type of data used is primary data. The results of the study show that, partially, social media, product quality, and product price have a positive and significant effect on the purchase intentions of Surakarta students regarding halal cosmetics (skincare).